Some Aspects of the Pure Theory of Capital - Samuelson, Paul A. (Quarterly Journal of Economics, 1937)
Definition of an investment account, 469. — Relationships between capitalized value, depreciation, and income holding at all times under any rate of discount, 470. — Necessary equality between capital invested and value of investment account derived by capitalization, 474.— Definition and derivation of internal rate of interest; its relation to market rate, 475. — Identification under ideal conditions of market value of investment account with capitalized value, 477.— Problem of optimum determination of variables; maximization of internal rate vs. maximization of present value of assets, 478.— Demonstration that all principles remain invariant under a varying interest rate, 483.— Mathematical appendix I, 488, — Mathematical appendix II, 492.